The Ongoing Evolution of Adaptive Co-management: Taking Stock of Trends, Gaps and Opportunities for Research and Practice - Ryan Plummer; Samantha Witkowski; Derek Armitage (Environmental Management, 2026)

Testing the Influence of Tactics on an Intention to Participate in an Environmental Management Collaborative - Shannon Heaney; Ryan Plummer; Julia Baird; Amy Bowen; Gillian Dale (Environmental Management, 2024)

Investigating the risky dilemma of regional flood planning: The case of the Wolastoq | Saint John River Basin, Canada - Bridget McGlynn; Ryan Plummer; Julia Baird; Angela M. Guerrero (Environmental Science & Policy, 2024)

Third-generation adaptive capacity assessment for climate-resilient development - Carmen E. Elrick-Barr; Ryan Plummer; Timothy F. Smith (Climate and Development, 2023)

Soil health and management matters: A survey of field tree nursery producers - Darby McGrath; Ryan Plummer; Charlene Williams; Bridget McGlynn (Journal of Environmental Management, 2023)

The role of a nature-based program in fostering multiple connections to nature - Julia Baird; Gillian Dale; Jennifer M. Holzer; Garrett Hutson; Christopher D. Ives; Ryan Plummer (Sustainability Science, 2022)
Reconnecting to nature is imperative for the sustainability of humans on Earth, offering a leverage point for system change. Connections to nature have been conceptualized as a typology of five types as follows: material; experiential; cognitive; emotional; and, philosophical, ranging from relatively shallow to deeper connections, respectively. Educational programs that immerse individuals in nature have been designed to build an appreciation for places travelled, awareness of environmental issues and to promote pro-environmental behaviours. Using quantitative and qualitative data from 295 individuals who participated in National Outdoor Leadership School (NOLS) programs ranging from 14 to 90 days, we tested hypotheses to understand whether and to what extent NOLS influenced the five types of connections to nature. We further investigated whether deeper connection types were associated with greater intentions for pro-environmental behaviours. Findings showed that individuals generally reported greater connections to nature after the NOLS program, with emotional and material connections increasing the most. While intentions for pro-environmental behaviour increased from pre- to post-program, deeper connections to nature did not correspond to greater intention for pro-environmental behaviour. The strongest predictor of intention for pro-environmental behaviour was a cognitive connection, though an emotional connection was also a significant predictor. Ultimately, we found that the NOLS program fosters multiple connections to nature and increases intentions for pro-environmental behaviour. We call for more research to understand the relationships among connection to nature types and how those interactions may influence intentions for pro-environmental behaviour—in nature-based educational programs and in other contexts.

Assessing Factors of Environmental Stewardship Success: Organizational Perceptions from the Niagara Region of Ontario, Canada - Brooke Kapeller; Ryan Plummer; Julia Baird; Marilyne Jollineau (Environmental Management, 2022)

Correction to: Transdisciplinary partnerships for sustainability: an evaluation guide - Ryan Plummer; Jessica Blythe; Georgina G. Gurney; Samantha Witkowski; Derek Armitage (Sustainability Science, 2022)

Transdisciplinary partnerships for sustainability: an evaluation guide - Ryan Plummer; Jessica Blythe; Georgina G. Gurney; Samantha Witkowski; Derek Armitage (Sustainability Science, 2022)
Transdisciplinary research, in which academics and actors from outside the academy co-produce knowledge, is an important approach to address urgent sustainability challenges. Indeed, to meet these real-world challenges, governments, universities, development agencies, and civil society organizations have made substantial investments in transdisciplinary partnerships. Yet to date, our understanding of the performance, as well as impacts, of these partnerships for sustainability is limited. Here, we provide a guide to assess the performance and impacts of transdisciplinary partnerships for sustainability. We offer key steps to navigate and examine the partnership process for continuous improvement, and to understand how transdisciplinary partnership is contributing to sustainable futures.

Leave or Die: Dispersal of Red-Bellied Mudsnakes (Farancia abacura) from their Home Ranges in an Isolated Wetland - Michael V. Plummer; Caleb S. O’Neal; Steven M. Cooper; Ryan Stork; Nathan E. Mills; Aric B. McKinney (Wetlands, 2020)

The Inner-Workings of Collaboration in Environmental Management and Governance: A Systematic Mapping Review - Alison Feist; Ryan Plummer; Julia Baird (Environmental Management, 2020)

Examining Collaborative Processes for Climate Change Adaptation in New Brunswick, Canada - Alison Feist; Ryan Plummer; Julia Baird; Simon J. Mitchell (Environmental Management, 2020)

Working at the “speed of trust”: pre-existing and emerging social ties in wildfire responder networks in Sweden and Canada - Örjan Bodin; Daniel Nohrstedt; Julia Baird; Robert Summers; Ryan Plummer (Regional Environmental Change, 2019)

Participatory evaluation for adaptive co-management of social–ecological systems: a transdisciplinary research approach - Micaela Trimble; Ryan Plummer (Sustainability Science, 2019)

How Does Socio-institutional Diversity Affect Collaborative Governance of Social–Ecological Systems in Practice? - Julia Baird; Ryan Plummer; Lisen Schultz; Derek Armitage; Örjan Bodin (Environmental Management, 2019)

Emergence of Collaborative Environmental Governance: What are the Causal Mechanisms? - Julia Baird; Lisen Schultz; Ryan Plummer; Derek Armitage; Örjan Bodin (Environmental Management, 2019)

Analysis of Swedish Forest Owners’ Information and Knowledge-Sharing Networks for Decision-Making: Insights for Climate Change Communication and Adaptation - Karin André; Julia Baird; Åsa Gerger Swartling; Gregor Vulturius; Ryan Plummer (Environmental Management, 2017)

Collaborative governance for climate change adaptation in Canada: experimenting with adaptive co-management - Julia Baird; Ryan Plummer; Örjan Bodin (Regional Environmental Change, 2016)

Problematizing Water Vulnerability Indices at a Local Level: a Critical Review and Proposed Solution - Danuta de Grosbois; Ryan Plummer (Water Resources Management, 2015)

Science–policy processes for transboundary water governance - Derek Armitage; Rob C. de Loë; Michelle Morris; Tom W. D. Edwards; Andrea K. Gerlak; Roland I. Hall; Dave Huitema; Ray Ison; David Livingstone; Glen MacDonald; Naho Mirumachi; Ryan Plummer; et al. (Ambio, 2015)

Social Network Analysis of Multi-level Linkages: A Swedish Case Study on Northern Forest-Based Sectors - E. Carina H. Keskitalo; Julia Baird; Emmeline Laszlo Ambjörnsson; Ryan Plummer (Ambio, 2014)

A Systematic Review of Water Vulnerability Assessment Tools - Ryan Plummer; Rob de Loë; Derek Armitage (Water Resources Management, 2012)

Co-management of Natural Resources: A Proposed Framework - Ryan Plummer; John Fitzgibbon (Environmental Management, 2004)